CIVIL MARRIAGE AND REGIME OF MARRIAGE AND THE RECENT DECISION OF THE SUPERIOR COURT OF JUSTICE ABOUT THE CHANGE IN THE REGIME OF ASSETS (REMUNOM, 2024)
The present article is a study on the constant marriage regimes in our legal system, the general objective is to analyze the subject with a basis in Brazilian legislation in depth in order to elucidate doubts about it. The specific objectives are to verify and explain the differences between the different marriage regimes, and their peculiarities as well as each property regime and its numerous changes with the new legislation, the Brazilian civil code. In the current Brazilian legal system, civil legislation establishes four different models of matrimonial property regimes. Are they: Partial communion, separation of goods, universal communion and final participation in the aquestos. Let's look at each one clearly and objectively.